STOCK ESTIMATION FOR MUD CRAB (Scylla paramamosain) FROM THE KUBU VILLAGE CATCH, KUBU DISTRICT, KUBU RAYA REGENCY - ABIDIN, OKTAVIANA ZAINAL; SOETIGNYA, WIDADI PADMARSARI; MULYADI, AHMAD (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACT  Mud crab (Scylla paramamosain.) is a commodity that has the potential of high economic value. This study aims to estimate the stock crab (S. paramamosain) based on the width frequency distribution of the carapace, carapace width relationship with weight, growth, mortality and the rate of exploitation of crab. Data analysis was donemanually and used FISAT II Ver 1.2.2 in 2005 issued by FAO-ICLARM. This research was carried out between September and December 2018. The data collected in this research consist in the number of catches’ measurement of carapace width, weight and sex for mangrove crabs (S. paramamosain). Crab samples obtained amounted to 306 birds. The results of this study is the frequency of the highest crab in width from 109,5 to 114, 5 (mm). Wide and heavy relationship crab showed isometric growth pattern (b= 2,86). By Von Bertalanffy growth parameters are Lt= 177 (1-e  -0,37 (t + 0,56264)). Total mortality (Z) 0,605, natural mortality (M) 0,466 and fishing mortality (F) 0,139. The rate of exploitation (E) S. paramamosain are 0,229 so that said utilization is still below the optimal (under-exploited). Keywords: Exploitation, Growth, Mortality